(untitled) (Research in Agriculture Livestock and Fisheries, 2016)
A survey was conducted to determine the effect of climate change on crop production and water quality in 12 villages of Deluty and Garaikhali unions under Paikgacha upazila of Khulna district, Bangladesh. Total of 100 farmers were interviewed using a pre-tested questionnaire. The climatic hazards as reported on the study area are salinity, cyclone, drought, hailstorm, river erosion and waterlogging, of them salinity is the most dominant hazard. Due to salinity the cropping system has undergone changes. Many crops and varieties have been either extinct or their cultivation has come down. Both soil and water are severely affected by salinity. Most of the farmers (90%) use pond water for irrigation and the majority farmers use pond and rain waters for drinking purpose. Results of the present study serves as a good basis for in-depth study to achieve successful crop production in the south west coastal area of Bangladesh. Res. Agric., Livest. Fish.3(3): 369-378, December 2016